New records of genera and species of moth flies (Diptera, Psychodidae: Psychodinae) from Morocco - Imane Saidoun; Mohamed Amin El Mouden; Samia Boussaa; Boutaïna Belqat (Journal of Insect Biodiversity and Systematics)
A survey of moth flies in mountainous and desert areas of Morocco revealed 20 species, five genera with 10 species which are recorded from the country for the first time, six of which (Atrichobrunettia (Mirousiella) graeca Ježek & Goutner, 1993, Lepiseodina rothschildi (Eaton, 1912), Mormia revisenda (Eaton, 1893), Pericoma (Pachypericoma) fallax Eaton, 1893, Pericoma (Pericoma) trifasciata (Meigen, 1804), and Psychoda (Chodopsycha) divaricata Duckhouse, 1968), alongside two genera, Atrichobrunettia Satchell, 1953 and Lepiseodina Enderlein, 1937), are new to North Africa. In addition, three species and one species are new to the Rif and the Beni Snassen mountains, respectively, seven species are cited for the first time in the Atlas region and one species is new to the Sahara region. Information on the habitats of the 20 species is provided. The survey increases the biodiversity of moth flies in Morocco to 37 species.